Peranan Kecerdasan Emosi dan Dukungan Sosial terhadap Kesejahteraan Psikologis Siswa SMP Terbuka di Cirebon - Triana Indrawati (Edukasia Islamika : Jurnal Pendidikan Islam, 2017)
This study aims to investigate psychological well-being of SMP Terbuka students which is predicted influenced by emotional intelligence and social support. The initial assumption proposed in this study is that emotional intelligence and social support can predict the psychological well-being. The samples taken in this study were 100 students of SMP Terbuka Cirebon. They were taken by using cluster random sampling. The measuring instruments used in the study consist of 3 scales. First, the scale of psychological well-being which was based on the aspects of Ryff (1989) consists of 30 items with a correlation coefficient from 0,312 to 0,590 and an alpha coefficient 0,887. Second, the scale of emotional intelligence which was based on aspects of the Goleman (2002) consists of 29 items with a correlation coefficient from 0.331 to 0,631 and an alpha coefficient 0.897. Third, the scale of social support which was based on aspects of Cohen and Syme (1985) consists of 28 items with correlation coefficient from 0,350 to 0,624 and an alpha coefficient 0,895. The method of data analysis used in this study was multiple regression analysis. Regression analysis showed F = 63,883, p = 0,001 (p<0.05) and R2 = 0,568, which means emotional intelligence and social support can predict psychological well-being of SMPT Terbuka students.